Post-Harvest Loss in Sub-Saharan Africa : What Do Farmers Say? - Kaminski, Jonathan; Christiaensen, Luc (World Bank, Washington, DC, 2014)
The 2007-2008 global food crisis has renewed interest in post-harvest loss, but estimates remain scarce, especially in Sub-Saharan Africa. This paper uses self-reported measures from nationally representative household surveys in Malawi, Uganda, and Tanzania. Overall, on-farm post-harvest loss adds to 1.4-5.9 percent of the national maize harvest, substantially lower than the Food and Agriculture Organization's post-harvest handling and storage loss estimate for cereals, which is 8 percent. Post-harvest loss is concentrated among less than a fifth of households. It increases with humidity and temperature and declines with better market access, post-primary education, higher seasonal price differences, and possibly improved storage practices. Wider use of nationally representative surveys in studying post-harvest loss is called for.